STUDY OF MORPHOMETRIC CHANGES IN LIVER PARENCHYMA IN ANTI-INFLAMMATORY DRUG POLYPRAGMASIA - Usanov , Sanjar; Abduraimov , Zafarjon (Medical science of Uzbekistan, 2024)
Objective: To study morphometric changes in the structure of the liver of white rats with polypharmacy with anti-inflammatory drugs. Methods: The study was carried out on 50 male white rats, weighing from 210 to 320 g, kept in a vivarium with a standard diet, free access to water, and a normal lighting regime. The animals were divided into 3 groups. Results: When comparing the morphometric parameters of the rats of the 3rd group with those of the 2nd group, a significant decrease was found. The area of the hepatic cell decreased 5.14%, 5.05%, 3.19% and 3.02%, the outer diameter of the central vena decreased 8.13%, 6.11%, 4.08% and 3.42%, the diameter of the biliary duct decreased by 6.33%, 5.09%, 3.12% and 3.08%, the outer diameter of the arterial decreased by 7.12%, 5.07%, 5.03% and 4.48%, the diameter of the hepatic biliary duct decreased by 4.47%, 4.04%, 3.07% and 2.31%. Conclusions. The presence of the effect of polypharmacy by anti-inflammatory drugs on the liver indicates that polypharmacy has a detrimental effect on urinary excretion, reduces biliary excretion and has a sufficient level of risk for the body.